Uso de contraceptivos orais entre mulheres de 18 a 49 anos: inquérito populacional telefônico - Daniele Aparecida Silva Correa (2012)
Women in reproductive age represent about 30% of the Brazilian population. The government actions directed to them are related to family planning ensuring full and open access to information and contraceptive methods. The Ministry of Health adopts clinical eligibilitycriteria (clinical procedures based on scientific evidence to guide the prescription and use those methods to ensure their effectiveness and to avoid damaging the health of those who use them) developed by the World Health Organization. Among methods for family planning, theworld's most used is the oral contraceptive (OC). OBJECTIVES: To know the using patterns of contraceptives in Brazilian women and evaluate the appropriate appliance of oral contraceptives according to the clinical eligibility criteria that ascertains the occurrence of iniquities. METHODS: A population-based epidemiological study, which used cross-sectionaldescriptive secondary data from the VIGITEL, which collects information on risk factors for chronic diseases and protection of the population through telephone interviews. It considers the Brazilian female population 18-49 years, living in 26 state capitals and the Federal District, attended by fixed telephone line on the year 2008 (n = 21074). The estimations were calculated by observing an accuracy range of 95%. Educational level was used as proxy of socioeconomic status for the inequities analysis. The inappropriate use of oral contraceptives is defined with the presence of the following factors: hypertension and / or smoking in womenover 35 years and / or cardiovascular disease. Due to the probabilistic nature of the samples, weights were used for correction and inferences. All information is self reported and informed consent was replaced by verbal consent. RESULTS: Approximately 70% of women use somekind of family planning method, the OC is the most used (33.8%). Hypertension (15.5%) and smoking (12.2%) were the main risk factors for cardiovascular disease presented in OC users and are also contraindications for its use. The contraindicated use was present in 13.1% of the population. There were no differences in the proportions between regions, however the analysis by capital, thirteen of them are above the overall national average and almost all of them concentrated in the Northeast and North region. The inappropriate use of OC is higheramong women with less education. Its proportion in Brazil should be considered high, therefore, actions related to health education and smoking cessation should be prioritized, especially on those specific group.